The role of pore size on vascularization and tissue remodeling in PEG hydrogels - Chiu, Yu-Chieh; Cheng, Ming-Huei; Engel, Holger; Kao, Shu-Wei; Larson, Jeffery C.; Gupta, Shreya; Brey, Eric M. (Biomaterials, 2011)
Vascularization is influenced by the physical architecture of a biomaterial. The relationship between pore size and vascularization has been examined for hydrophobic polymer foams, but there has been little research on tissue response in porous hydrogels. The goal of this study was to examine the role of pore size on vessel invasion in porous poly(ethylene glycol) (PEG) hydrogels. Vascularized tissue ingrowth was examined using three-dimensional cell culture and rodent models. In culture, all porous gels supported vascular invasion with the rate increasing with pore size. Following subfascia implantation, porous gels rapidly absorbed wound fluid, which promoted tissue ingrowth even in the absence of exogenous growth factors. Pore size influenced neovascularization, within the scaffolds and also the overall tissue response. Cell and vessel invasion into gels with pores 25-50 μm in size was limited to the external surface, while gels with pores larger pores (50-100 and 100-150 μm) permitted mature vascularized tissue formation throughout the entire material volume. A thin layer of inflammatory tissue was present at all PEG-tissue interfaces, effectively reducing the area available for tissue growth. These results show that porous PEG hydrogels can support extensive vascularized tissue formation, but the nature of the response depends on the pore size.
Gesehen am 28.06.2022